ANALYSIS OF LEARNING ACTIVITIES AND OUTCOMES THROUGH STATIC FLUID LKPD BASED ON VIRTUAL LAB ON STUDENTS OF MAN 1 JEMBER - Helmi Aminuddin; Anisa Septi Pratiwi; Salfa Zahroh Ahadah; Ellyani Eka Putri; Subiki Subiki; I Ketut Mahardika (Jurnal Pembelajaran Sains, 2021)
Static fluid material is one of the materials in school where some students still have difficulty understanding concepts. The learning process using LKPD is more effective than without using LKPD because the use of LKPD allows students to be active in learning activities. The research method used by the author is descriptive qualitative. This study used pretest and posttest to determine the development of students' science process skills. Based on the results of the analysis that has been carried out, it has been proven that the virtual lab-based LKPD has a positive effect on the activities and learning outcomes of MAN 1 Jember students. This is evidenced by the post-test value which is higher than the pretest value. Besides that, With LKPD students become more active and have a higher interest than without using LKPD. Based on the analysis that has been done, it can be concluded that the use of Static Fluid LKPD has a positive influence on the activities and learning outcomes of MAN 1 Jember students.